Gravity inversion constrained by OBS receiver function reveals crustal structure in Ryukyu Trench - Yang, Tingwei; Xu, Ya; Du, Nanqiao; Xu, Tao; Cao, Danping; Nan, Fangzhou; Chu, Wei; Liang, Ce; Hao, Tianyao (Frontiers in Earth Science, 2023)
The Ryukyu Trench is located in the northern Philippine Sea. The subduction of the Philippine Sea Plate to the Eurasia Plate along the Ryukyu Trench in the NNW direction leads to extremely complex tectonic processes such as subduction, collision, accretion, and back-arc expansion. It is of great significance to obtain the crustal structure of the Ryukyu Trench for understanding the crustal deformation characteristics, subduction direction and the scale of the Philippine Sea Plate. The ocean bottom seismometer (OBS) could provide important information on the deep structure of the oceanic area, and the wide coverage of gravity anomaly can provide more constraints for the regional crustal structure. In this study, we put the time-delay term of the sedimentary layer into the H-κ stacking formula, which eliminates the influence of the sedimentary layer in traditional H-κ stacking. Based on the accurate crustal thickness at OBS locations, a gravity inversion method is proposed to solve the problem of non-uniqueness in gravity data and limited distribution of OBSs. By using this method, we obtain a crustal structure with higher resolution than Crust1.0 model in Ryukyu Trench. The results show that the crustal thickness in the Ryukyu Trench region thickens along the NNW subduction direction, revealing that the Philippine Plate’s subduction direction towards the Eurasian Plate is in the NNW direction.